Comprehensive Obstetric Care For Mrs. I G1P0A0 Gestational Age 28 Weeks 4 Days Of Delivery, Postpartum, Newborn And Family Planning At Pratama Kita Berastagi Clinic In 2022 - Eka Permatasari Purba (SEAN Institute, 2023)
This study focused on comprehensive obstetric care provided to Mrs. I, a primigravida (G1P0A0) with a gestational age of 28 weeks 4 days, ranging from childbirth, postpartum, newborn care, to family planning counseling. The research location is Pratama Kita Berastagi Clinic in 2022. Through the case study method and qualitative approach, this research seeks to understand Mrs. I's experience and special needs in each phase she went through. The results showed that comprehensive midwifery care played an important role in improving the well-being of Mrs. I and her baby. The interventions provided during labor guarantee a smooth delivery process and minimize the risk of complications. During the postpartum, emotional support and education about self-care and newborns are crucial. Family planning counseling after childbirth also helped Mrs. I and her husband make the best decisions for their family's future. This study recommends the importance of a comprehensive approach in midwifery care to ensure the best quality of care for pregnant women, newborns, and family planning. These findings are expected to be a reference for clinics and other health practitioners in providing holistic midwifery care.